Egypt Strategy Support Program workshop: Goal, objectives and procedures - Ecker, Olivier (2016)
Presentation by Olivier Ecker, Research Fellow at the International Food Policy Research Institute (IFPRI), on March 2, 2016 in Cairo, Egypt